Meeting the demands of the 21st century English Language learning through PBL-LcCRAFT - Suraini Mohd-Ali,; Haliza Harun,; Normazla Ahmad Mahir,; Norhaili Massari,; Noor Saazai Mat Saad,; Simkin, Keith (Penerbit Universiti Kebangsaan Malaysia, 2018)
Problem-Based Learning (PBL) Language Case Crafting (PBL-LcCRAFT) Model is a new PBL case design guide for language practitioners to craft PBL cases specifically for English Language teaching and learning. This paper describes five significant components in this new model that complement the 21st century learning skills. Data illustrated in this paper were drawn from an action research project on PBL case design training and model for English language practitioners. The four steps in the action research approach namely plan, act, observe and reflect were closely followed within two cycles of the research procedure. Data collection tools were observation checklist and focus group interviews with a group of English Language practitioners. The collected data were then analysed using content analysis for emerging themes and the findings were used to develop the new model (PBL-LcCRAFT). The outcome of this study is the new model which is a guide for crafting PBL cases specifically for languages. This paper discusses five interrelated components in the new model (Ill-structuredness, Language in-use, Researching, Reasoning and Reflecting) which language practitioners considered as significant components in crafting language cases. The key findings presented here are the five interrelated components in PBL-LcCRAFT that have assisted the practitioners to craft cases and the symbiosis between these five components with the 21st century skills (i.e. knowledge, creativity, collaboration, critical thinking and communication skills).